2016
DOI: 10.2527/jas.2016-0440
|View full text |Cite
|
Sign up to set email alerts
|

Lipid digestibility and energy content of distillers' corn oil in swine and poultry1

Abstract: Two experiments were conducted to determine the DE and ME and apparent total tract digestibility of ether extract of 3 distillers' corn oil (DCO; 4.9, 12.8, or 13.9% free fatty acids [FFA]) samplescompared with a sample of refined corn oil (CO; 0.04% FFA) and an industrially hydrolyzed high-FFA DCO (93.8% FFA) in young pigs and growing broilers. In Exp. 1, 54 barrows (initial age = 28 d) were fed a common diet for 7 d and then fed their allotted dietary treatment (either 100% basal diet or 1 of 5 test diets co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 53 publications
6
17
1
9
Order By: Relevance
“…The FA profile of CWG, SO, and PO sources evaluated in this study were similar to published values (O'Brien, 2009;NRC, 2012) as shown in Table 1. The 2 DCO samples had FA profiles that resembled refined corn oil (NRC, 2012), and similar to those from recently published data evaluating DCO (Moreau et al, 2011;Winkler-Moser and Breyer, 2011;Kerr et al, 2016). As expected, the FFA content of the 2 refined oils (PO and SO) were low compared to that for CWG and the 2 DCO samples, with the 2 DCO samples having a similar FFA content to those reported previously (Moreau et al, 2010;Kerr et al, 2016).…”
Section: Corn Oil and Diet Compositionsupporting
confidence: 86%
See 2 more Smart Citations
“…The FA profile of CWG, SO, and PO sources evaluated in this study were similar to published values (O'Brien, 2009;NRC, 2012) as shown in Table 1. The 2 DCO samples had FA profiles that resembled refined corn oil (NRC, 2012), and similar to those from recently published data evaluating DCO (Moreau et al, 2011;Winkler-Moser and Breyer, 2011;Kerr et al, 2016). As expected, the FFA content of the 2 refined oils (PO and SO) were low compared to that for CWG and the 2 DCO samples, with the 2 DCO samples having a similar FFA content to those reported previously (Moreau et al, 2010;Kerr et al, 2016).…”
Section: Corn Oil and Diet Compositionsupporting
confidence: 86%
“…The 2 DCO samples had FA profiles that resembled refined corn oil (NRC, 2012), and similar to those from recently published data evaluating DCO (Moreau et al, 2011;Winkler-Moser and Breyer, 2011;Kerr et al, 2016). As expected, the FFA content of the 2 refined oils (PO and SO) were low compared to that for CWG and the 2 DCO samples, with the 2 DCO samples having a similar FFA content to those reported previously (Moreau et al, 2010;Kerr et al, 2016). Each lipid source was also analyzed for moisture (M), insoluble (I), and unsaponifiables (U) because of research suggesting that MIU should be considered for improving the accuracy of predicting DE and ME from various lipid sources (Wiseman et al, 1992;Blanch et al, 1996;Vila and Garcia, 1996a,b;Rosero et al, 2015a).…”
Section: Corn Oil and Diet Compositionsupporting
confidence: 80%
See 1 more Smart Citation
“…Tłuszcze (lipidy) w organizmach zwierząt pełnią funkcję zarówno energetyczną, jak i budulcową (strukturalną) (11,12,29,39,42,47,60,66). Tłuszcz jest komponentem wysokoenergetycznym, zawierającym około 35 MJ/kg mieszanki paszowej (19).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…Esse fator depende se o grão de milho destinado para a produção de etanol estiver contaminado por esses metabólitos, já que as micotoxinas não são destruídas durante o processamento. Deve-se cuidar com o armazenamento deste coproduto e do grão, pois DDGS tem seu teor de extrato etéreo alterado, acarretando na redução da energia do mesmo e criando uma nova fonte de gordura para se utilizar nas dietas(Dozier et al, 2017;Kerr et al, 2016). Essas melhorias realizadas em relação ao processamento trouxeram novos coprodutos, os quais podem ter altas quantidades de proteína (DDG High Protein -DDG HP), fibra e com níveis de 5, 8, 10 a 15% de gordura (DDGS Low Oil e DDGS High Oil) (NRC.…”
unclassified